Risk Factors of Relapse After Smoking Cessation: Results in China Family Panel Studies From 2010 to 2018 - Naifan Hu; Zhenfan Yu; Yurun Du; Jiangping Li; Jiangping Li (Frontiers Media S.A., 2022)
BackgroundTobacco use is still highly prevalent globally in spite of the tobacco control efforts made by the governments. In view of the harm of smoking and relapse after smoking cessation, the purpose of this study is to establish a competitive risk model to determine potential risk factors for smoking relapse.MethodsThe population-based cohort of ex-smokers over the age of 18 years was obtained from the China Family Panel Studies (CFPS) database from 2010 to 2018. Competing risk models were conducted to identify the risk factors for relapse.ResultsA total of 1,019 subjects were included in this study, of which 311 (30.52%) subjects relapsed during the follow-up period. A multivariate analysis indicated that age < 40 years [hazard ratio (HR) 19.142; 95% CI: 10.641-34.434, p < 0.01], cohabitation (HR: 1.422; 95% CI: 1.081-1.87, p = 0.01), and often depression [HR 1.422; 95% CI, (1.081-1.87), p = 0.01] were associated with a great risk of relapse while the age of quitting smoking < 60 years (HR: 0. 436; 95% CI: 0.229-0.831, p < 0.01) and joining the Chinese Communist Party (CCP) (HR 0.611; 95% CI: 0.397-0.939, p = 0.03) were reduced risk factors for relapse.ConclusionsApproximately 3 in 10 ex-smokers were observed to relapse. There are various risk factors for relapse as well. In the face of such a serious situation, it is urgent to take action to control smoking.